2011
DOI: 10.1124/jpet.111.180638
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 5-Hydroxytryptamine 7 Receptors in the Phencyclidine-Induced Novel Object Recognition Deficit in Rats

Abstract: The role of 5-hydroxytryptamine (serotonin) (5-HT) 7 receptor antagonism in the actions of atypical antipsychotic drugs (APDs), e.g., amisulpride, clozapine, and lurasidone, if any, is uncertain. We examined the ability of 5-HT 7 receptor antagonism alone and as a component of amisulpride and lurasidone to reverse deficits in rat novel object recognition (NOR) produced by subchronic treatment with the N-methyl-D-aspartate receptor antagonist phencyclidine (PCP), and we examined the ability of supplemental 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 46 publications
7
80
0
Order By: Relevance
“…A growing body of evidence supports the concept for targeting 5-HT 7 antagonism as a possible mechanism for the treatment of cognitive deficits and a potential target for novel anxiolytic and antidepressant drugs (Hedlund et al, 2005;Abbas et al, 2009;Mnie-Filali et al, 2009;Horiguchi et al, 2011). In conclusion, the results reported here suggest that the procognitive effect of 5-HT 7 receptor antagonism (Gasbarri et al, 2008;Horiguchi et al, 2011) may result from enhancement of NMDAR function.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…A growing body of evidence supports the concept for targeting 5-HT 7 antagonism as a possible mechanism for the treatment of cognitive deficits and a potential target for novel anxiolytic and antidepressant drugs (Hedlund et al, 2005;Abbas et al, 2009;Mnie-Filali et al, 2009;Horiguchi et al, 2011). In conclusion, the results reported here suggest that the procognitive effect of 5-HT 7 receptor antagonism (Gasbarri et al, 2008;Horiguchi et al, 2011) may result from enhancement of NMDAR function.…”
Section: Discussionsupporting
confidence: 56%
“…The electrophysiological results reported here are consistent with the behavioral effects of these compounds in schizophrenia models. Horiguchi et al (2011) have found that lurasidone, clozapine, and SB-269970, but not haloperidol, improve the impairment in NOR induced by subchronic PCP treatment. Moreover, the ability of lurasidone to reverse the PCP-induced NOR deficit is blocked by the 5-HT 7 agonist AS19 (Horiguchi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations